1978
DOI: 10.1227/00006123-197809000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Pituitary Function before and after Trans-sphenoidal Microsurgical Resection of Pituitary Tumors

Abstract: Anterior pituitary lobe function was measured pre- and postoperatively in 40 patients with pituitary tumors who were managed surgically by the trans-sphenoidal approach. Of 23 patients with normal anterior lobe function preoperatively, 21 (91%) were normal postoperatively. Of 17 preoperatively impaired patients, 7 (40%) regained normal function, 3 (18%) improved, 4 (24%) remained the same, and 3 (18%) were further impaired by the surgery. In this small series, the likelihood of recovery of pituitary function v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…Of the patients with deficits in one axis or more preoperatively, 37% improved and 6% worsened. McLanahan, et al, 9 reported on 40 patients with tumors of all types and of varying sizes. They found that of the 12 patients with tumors less than 1 cm in size who had normal pituitary function, all retained normal function after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Of the patients with deficits in one axis or more preoperatively, 37% improved and 6% worsened. McLanahan, et al, 9 reported on 40 patients with tumors of all types and of varying sizes. They found that of the 12 patients with tumors less than 1 cm in size who had normal pituitary function, all retained normal function after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…reporting decreased anterior pituitary function in 12.5% of patients [182–184]. Anterior pituitary insufficiency is more likely to occur in macroadenomas and preservation of normal anterior pituitary tissue can be sufficient to maintain pituitary function [155,183,185]. Pituitary stalk manipulation during resection of microadenomas may result in temporary diabetes insipidus (DI) postoperatively in as many as 1.6–60% of trans-sphenoidal cases.…”
Section: Complicationsmentioning
confidence: 99%
“…The group of dentists comprised nine men who had been practising for an average of28 (range [25][26][27][28][29][30] years, and who were still working as dentists. In this group, no information was available conceming earlier B Hg or U Hg concentrations.…”
mentioning
confidence: 99%